MEDIA PERMAINAN BAHASA DALAM PEMBELAJARAN BAHASA ARAB - Suci Rahmawati; Ahmad Yani; Siti Hindun; Lutfiyah Hakim (Al Naqdu, 2022)
Arabic is a boring subject for most students. Especially with the added lack of ability of a teacher in conditioning the learning process. The task of the Arabic language teacher is to optimize learning in the classroom by using several innovations. It can be seen that the saturation of students in learning, lack of focus, and the need for refreshment on the sidelines of the process of teaching and learning activities in the classroom are problems that occur in Arabic learning today. Of course, there are special ways for teachers to deal with these things. Seeing the background of the problems above, the researcher assumes that the role of language games in the process of teaching and learning activities for Arabic subjects can help teachers achieve better learning goals. Many language games can be applied by teachers, as a means of supporting students' success in learning Arabic. This study used qualitative methods to obtain the desired results, while in collecting data using observation and interview methods, students and Arabic teachers of SMPIT were the subjects of data collection. The purpose of this study is that students can master the four language skills in learning Arabic by using language game media to make it easier to understand. And from this study, it was found that using language game media in learning Arabic is very effective and very helpful for teachers to provide material to students.